Sistem Informasi Pendataan Masyarakat Kurang Mampu Berbasis Web di Kelurahan Cisalak - Fauzan Ardiansyah; Perani Rosyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Poverty is a complex problem that is influenced by various interrelated factors, including: income levels, health, education, and housing conditions. Data collection on the poor must be done well, therefore it should have a computerized system so that the data collection of the poor has parameters of income and housing conditions. To support the purpose of this research, the method used in making the information system is the Waterfall and Tools model that uses the PHP programming language, MySql Boostrap Database, and Macromedia Dreamweaver. The results of the research design in accordance with the research objectives are expected to help the poor data collection officers with an information system for collecting data on the poor using income parameters and housing conditions. This system can provide complete and accurate information in accordance with the criteria for the poor, which is displayed in pdf form, making it easier for officers and the community to identify optimally.